Is the Tradition of Nasal Packing Just an Illusion of Permanence or a Necessary Evil? - Mathialagan, Arulalan; Singh, Suyash; Jaiswal, Awadhesh Kumar; Manogaran, Ravi Sankar; Mishra, Prabhakar; Keshri, Amit Kumar (Indian Journal of Neurosurgery, 2021)
Background Nasal packing after an endoscopic endonasal approach (EEA) is a routine practice. There is a very urgent need for a level-I recommendation pertaining to the necessity of these packs and, if required, then the timing of its removal. However, the opponents of this practice mention its various disadvantages, among which infection is the most important. In our study, we have evaluated the bacteriological profile of the nasal packs, following endoscopic anterior skull base surgery.Materials and Methods Thirty consecutive cases (2017–18) of anterior skull base pathologies operated by EEA were included, and preoperative nasal swab and postoperative period, the nasal packs were sent for microbiological culture. The colony of bacteria grew, and clinical condition, histopathology and demographic profile of the patients were noted.Results Of the 30 patients, 40% (n = 12) showed an increase in nasal bacterial flora after packing, with methicillin-sensitive coagulase negative Streptococcus (MSCNS) in three patients, Escherichia fecalis (E. fecalis) in three patients, and methicillin-resistant coagulase negative Streptococcus (MRCNS) in two patients. Other rare organisms grew, including Acinetobacter baumanni with E. fecalis, Acinetobacter baumanni with MRCNS, Citrobacter koseni, and Escherichia fecium (E. fecium) with MRCNS and MRSA in one patient each.Conclusion Packing increases the bacterial load of the nasal cavity. This bacterial flora can be a potential source of meningitis. We advocate that packing should be avoided, and if at all required, should be removed within 3 days. A routine practice of nasal swab in the preoperative period and culture of the packs may give information on the possible organism that may cause meningitis and the appropriate antibiotic sensitivity of the organism.
Keywords: anterior skull base surgery; nasal packing; bacterial culture